The Acknowledgments in Student Theses: Eastern and Western Ideology - Putikadyanto, Agus Purnomo Ahmad; Rahmawati, Fithriyah; Setiadi, Asep (OKARA: Jurnal Bahasa dan Sastra, 2022)
People's ideologies in various Western and Eastern countries influence language use, including acknowledgment writing. This qualitative study attempts to establish Eastern and Western ideologies in the acknowledgments of the student's final projects using a critical discourse approach. Eastern ideology was examined through 57 acknowledgments of student theses from eastern countries (Indonesia, Malaysia, Saudi Arabia, and Singapore) written in Indonesian and English. In comparison, Western ideology was examined through 53 acknowledgments of student theses from western countries (United States of America, England, and Germany) written in English. The linguistic features of Fairclough and Santoso were used to reveal the Eastern and Western ideology found in the acknowledgments of students’ final projects. The findings revealed that the language used to acknowledge eastern ideology was rigid. In Muslim-majority countries, gratitude to God comes first, and there are expressions of gratitude to parents. Gratitude expressions found in some eastern countries were based on the hierarchy of positions. The Western ideology in the acknowledgment, on the other hand, can be seen in the use of more expressive languages. Moreover, the acknowledgment format is not rigid and is arranged according to the hierarchy of works' contributions. The findings also indicate that identity has an impact on language.